Reliability Assessment of Pasar Baru and Plaza Bogor Buildings - Lutfi, Muhamad; Chayati, Nurul; Aulia, Rezkia Dizha; Yusup, Siska; Insan, Muhammad Khaerul (ASTONJADRO, 2026)
The Pasar Baru Bogor and Plaza Bogor buildings have been in operation for decades, so it is necessary to analyze the reliability of the buildings to ensure their structural and operational conditions. This research evaluates the physical reliability of both buildings through visual observation and concrete quality testing using the method Non-Destructive Test (NDT) with the tool Hammer Test Type N. The evaluation covers five main aspects: architecture, structure, utilities and fire protection, accessibility, and building and environmental planning. The results of the research on the Pasar Baru Bogor Building show that the reliability value of the architectural aspects is 83.30%, structure 93.06%, utilities and fire protection 42.50%, accessibility 68.25%, and building and environmental planning 63.46%, with a total reliability of 64.08% which is classified as "Not Reliable." Concrete compressive strength testing shows results between 25.69 MPa and 65.81 MPa, so the structure is declared "Safe". The Plaza Bogor Building has an architectural aspect reliability value of 89.00%, structure 100%, utilities and fire protection 61.67%, accessibility 72%, and building and environmental planning 66.60%, with a total reliability of 76.66% which is categorized as "Less Reliable." Concrete compressive strength testing shows results between 23.72 MPa and 65.84 MPa, which meets structural reliability standards. Thus, the Pasar Baru Bogor Building has low reliability although the building structure is safe, while the Plaza Bogor Building has good structural reliability, but other aspects require improvement to increase reliabilitymaximum.